James J. Dinsmore letter to Thomas H. Kent regarding field notes, February 24, 1982 - Dinsmore, James J.et al (1982)
Field notes were contributed by James J. Dinsmore in a letter to Thomas H. Kent. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of winter 1981-1982. Epson - sheet feed